GRIN2A and Schizophrenia: Scientific Evidence and Biological Mechanisms - Sheng, Xiao-Ming; Guan, Wei (Current Neuropharmacology, 2025)
Schizophrenia is a severe psychiatric disorder and a complex polygenic inherited disease that affects nearly 1% of the global population. Although considerable progress has been made over the past 10 years in the treatment of schizophrenia, antipsychotics are not universally effective and may have serious side effects. The hypofunction of glutamate NMDA receptors (NMDARs) in GABAergic interneurons has long been postulated to be the principal pathophysiology of schizophrenia. A recent study has shown that GRIN2A pathogenic variants are closely related to the aetiology of the disorder. GRIN2A encodes the GluN2A protein, which is a subunit of NMDAR. Most GRIN2A variants have been predicted to cause protein truncation, which results in reduced gene expression. Preclinical studies have indicated that GRIN2A mutations lead to NMDAR loss of function and substantially increase the risk of schizophrenia; however, their role in schizophrenia is not well understood. We hypothesise that the heterozygous loss of GRIN2A induces NMDAR hypofunction sufficient to confer a substantial risk of schizophrenia. Therefore, this review focuses on GRIN2A as a target for novel antipsychotics and discusses the mechanisms by which GRIN2A modulates antischizophrenic activities. Moreover, our review contributes to the understanding of the pathophysiology of schizophrenia to facilitate finding treatments for the cognitive and negative symptoms of schizophrenia.
Keywords: Schizophrenia